Biomass modified iron-chromium flow battery carbon cloth electrode and preparation method thereof

By modifying the biomass material of the carbon cloth electrode of the iron-chromium flow battery, the problem of insufficient electrode activity is solved, the electrochemical performance and cyclic stability of the battery are significantly improved, and higher energy efficiency and electrocatalytic activity are achieved.

CN119252943AActive Publication Date: 2025-01-03ZHONGHAI ENERGY STORAGE TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411416868.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-03
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing iron-chromium flow battery carbon cloth electrode has low electrochemical activity and insufficient catalytic activity, which limits the overall performance of the battery.

Method used

The carbon cloth is modified through high-temperature heat treatment, impregnation, high-temperature calcination and carbon thermal reduction technologies to form rich high-catalytic active sites, improve the conductivity of the electrode and the catalyst growth environment, and enhance the electrochemical performance.

Benefits of technology

It significantly improves the energy efficiency, Coulomb efficiency and cycling stability of the battery, increases the specific surface area of ​​the electrode and oxygen-containing functional groups, improves the kinetics and reversibility of the redox reaction, and delays the attenuation of the battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252943A_ABST
    Figure CN119252943A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flow battery energy storage, and particularly discloses a biomass-modified iron-chromium flow battery carbon cloth electrode and a preparation method thereof.The preparation method comprises the following steps that carbon cloth is washed with deionized water and then put into ethyl alcohol to be soaked, then ultrasonic washing is conducted in deionized water, and the carbon cloth is put into a drying oven to be dried; activating the carbon cloth by using high-temperature heat treatment; the preparation method comprises the following steps: adding biomass powder into deionized water, then adding an auxiliary agent, stirring the obtained mixture, and carrying out ultrasonic treatment to form precursor slurry; immersing the carbon cloth subjected to high-temperature heat treatment into the precursor slurry, treating by using an immersion method, and then drying the carbon cloth; the carbon cloth is taken out and subjected to high-temperature calcination in a tubular furnace under the protective atmosphere for carbon thermal reduction, and the biomass material modified carbon cloth electrode is obtained. The nitrogen doping effect is achieved on the surface of the carbon cloth after biomass modification, the effect of improving the electrochemical reaction activity of chromium ions can be achieved, and meanwhile the energy efficiency of the iron-chromium flow battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of liquid flow battery energy storage, and in particular to a biomass-modified iron-chromium liquid flow battery carbon cloth electrode and a preparation method thereof. Background Art

[0002] Due to the intermittent and random nature of renewable energy sources such as wind power and photovoltaic power generation, large-scale integration into the power grid will have a serious impact on the safe and stable operation of the power grid. Therefore, large-scale energy storage technology is urgently needed to achieve peak load shaving and valley filling of the power grid, thereby improving the power grid's ability to absorb renewable energy generation and solving problems such as wind and photovoltaic abandonment.

[0003] Iron-chromium flow battery is an energy storage technology with broad application prospects. Compared with traditional lead-acid batteries and lithium-ion batteries, flow batteries have significant advantages in life, efficiency and safety. ICFB uses iron and chromium as active materials to store and release energy through redox reactions in electrolyte solutions. This technology is particularly suitable for large-scale energy storage systems, such as grid peak regulation, renewable energy power generation supporting energy storage, etc.

[0004] In iron-chromium flow batteries, electrode materials are one of the key factors that determine battery performance. Carbon cloth electrodes have become a commonly used electrode material in flow batteries due to their high conductivity, good chemical stability and large specific surface area. However, carbon cloth electrodes themselves have some shortcomings, such as low electrochemical activity and low catalytic activity, which limit the overall performance of iron-chromium flow batteries. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a biomass-modified iron-chromium liquid flow battery carbon cloth electrode and a preparation method thereof. The carbon cloth is modified with biomass materials by using high-temperature heat treatment, impregnation method, high-temperature calcination, carbon thermal reduction method and other technologies, thereby providing abundant high catalytic activity sites for the redox reaction of the iron-chromium liquid flow battery electrolyte. The formed more oxygen-containing functional groups are used to promote the redox reaction of the iron-chromium liquid flow battery electrolyte, improve the conductivity of the carbon cloth electrode, optimize the growth environment of the catalyst, improve the electrochemical properties of the prepared electrode material, bring about a high degree of improvement in battery performance, and solve the problems mentioned in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a biomass-modified iron-chromium liquid flow battery carbon cloth electrode, comprising the following steps:

[0007] S1. Carbon cloth pretreatment: The carbon cloth is cleaned with deionized water, soaked in ethanol after cleaning, and then ultrasonically cleaned in deionized water. The carbon cloth after ultrasonic cleaning is placed in an oven to dry, and then activated by high-temperature heat treatment;

[0008] S2. Preparing a precursor slurry: adding biomass powder to deionized water, and then adding an auxiliary agent to obtain a mixture, stirring and ultrasonically treating the obtained mixture to form a precursor slurry;

[0009] S3, impregnation: immersing the carbon cloth after high temperature heat treatment into the precursor slurry, using an impregnation method for treatment, and then drying the carbon cloth;

[0010] S4, carbon thermal reduction: the carbon cloth obtained in step S3 is taken out, and carbon thermal reduction is performed by calcining at high temperature in a protective atmosphere in a tubular furnace to obtain a carbon cloth electrode modified by biomass material.

[0011] Preferably, in step S1, the carbon cloth is polyacrylonitrile PNV-based carbon cloth, rayon-based carbon cloth or petroleum asphalt-based carbon cloth; the soaking time in ethanol is 10 to 20 minutes; the ultrasonic cleaning time is 10 to 100 minutes; and the drying temperature in the oven is 30 to 150°C.

[0012] Preferably, in step S1, the high-temperature heat treatment of activated carbon cloth is to place the carbon cloth in a muffle furnace and perform high-temperature heat treatment in an atmosphere of one or more mixed gases of air, helium, nitrogen, argon, xenon, and neon; the temperature of the high-temperature heat treatment is 200-800°C, and the insulation time is 1-20h.

[0013] Preferably, in step S2, the biomass powder is one or more of grapefruit peel powder, tangerine peel powder, orange peel powder, and lemon peel powder, and the mass fraction of the biomass powder in the final precursor slurry is 1% to 30%.

[0014] Preferably, in step S2, the auxiliary agent acts as a binder, specifically one or more of sucrose, glucose, lactose, and fructose, with a concentration of 0.1 to 5 mol / L.

[0015] Preferably, in step S2, the stirring time is 10 to 100 min; the ultrasonic time is 10 to 100 min.

[0016] Preferably, in step S3, the dipping time is 10 to 200 minutes; when drying the carbon cloth, the drying temperature is 30 to 150° C., and the drying time is 1 to 20 hours.

[0017] Preferably, in step S4, during carbothermal reduction, the calcination temperature is 500-2000°C, the protective atmosphere is a mixed gas of one or more of helium, nitrogen, argon, xenon and neon, the heating rate during the reaction is 1-30°C / min, and the insulation time is 1-20h.

[0018] On the other hand, to achieve the above purpose, the present invention also provides the following technical solution: an electrode material prepared according to the above preparation method.

[0019] The beneficial effects of the present invention are:

[0020] 1) The present invention modifies and improves the carbon cloth electrode by using biomass materials, which shows higher energy efficiency, specific capacity, coulombic efficiency and more stable cycle performance in battery cycle compared with unmodified materials; it can effectively improve the electrochemical performance and catalytic activity of the electrode.

[0021] 2) The present invention utilizes biomass materials to prepare modified iron-chromium liquid flow battery electrode materials to improve battery performance. The method is simple, the raw material cost is low, and it is suitable for large-scale market preparation. It is a method that can promote the development of iron-chromium liquid flow batteries.

[0022] 3) The present invention conducts a carbon thermal reaction on the carbon cloth electrode modified with biomass materials. The carbon thermal reaction can form carbides embedded in the worm-like biomass pores on the electrode surface, thereby increasing the redox area at the electrode and providing a richer effective area for chemical reactions. In addition, a nitrogen doping effect is achieved on the surface of the carbon cloth after biomass modification, which can enhance the electrochemical reaction activity of chromium ions, while also enhancing the energy efficiency of iron-chromium flow batteries, slowing down battery capacity decay, and improving cycle stability. The specific surface area of ​​the modified electrode is increased, and more oxygen-containing functional groups, such as hydroxyl, aldehyde, carboxyl and other oxygen-containing functional groups, are introduced, thereby enhancing hydrophilicity, increasing the number of electrode active sites, and enhancing the kinetics and reversibility of redox reactions. The modified electrode has a high affinity for Fe 2+ / Fe 3+ and Cr 3+ / Cr 2+ The redox reaction has obvious electrocatalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of the worm-like biomass pores of the carbon cloth electrode modified by biomass materials prepared in Example 1 of the present invention;

[0024] Figure 2 This is a comparison chart of the coulombic efficiency of the carbon cloth electrode modified with biomass materials prepared in Example 1 of the present invention and the original unmodified carbon cloth electrode;

[0025] Figure 3 This is a comparison chart of the energy efficiency of the carbon cloth electrode modified by biomass materials prepared in Example 1 of the present invention and the original unmodified carbon cloth electrode;

[0026] Figure 4 This is a comparison chart of the voltage efficiency of the carbon cloth electrode modified by biomass materials prepared in Example 1 of the present invention and the original unmodified carbon cloth electrode;

[0027] Figure 5 This is a schematic diagram of the electrochemical performance of the carbon cloth electrode modified by biomass materials prepared in Example 1 of the present invention;

[0028] Figure 6 Schematic diagram of the electrochemical performance of the carbon cloth electrode modified by biomass materials prepared in Example 2 of the present invention;

[0029] Figure 7 This is a schematic diagram of the electrochemical performance of the carbon cloth electrode modified by biomass materials prepared in Example 3 of the present invention;

[0030] Figure 8 Schematic diagram of the electrochemical performance of the carbon cloth electrode modified by biomass material prepared in Example 4 of the present invention;

[0031] Fig. 9 This is a diagram showing the improvement in the hydrophilicity of the carbon cloth electrode modified by biomass materials prepared in the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] The carbon cloth was cleaned with deionized water and then soaked in alcohol for 10 minutes. The carbon cloth was ultrasonically cleaned with deionized water for 10 minutes and placed in an oven to be dried at 80°C to remove impurities on the surface of the carbon cloth.

[0035] The carbon cloth was placed in a muffle furnace and subjected to a high temperature heat treatment at 450°C in air for 5 hours. 15 g of grapefruit peel powder was added to 200.0 ml of deionized water and mixed with 10.0 ml of 0.2 M sucrose solution. The resulting mixture was stirred for 10 minutes and ultrasonically treated for 10 minutes to form a slurry, and the carbon cloth was immersed in the precursor slurry for 1 hour and then dried at 70°C.

[0036] The treated carbon cloth was placed in a tubular furnace high temperature device and subjected to high temperature heat treatment at 1200°C in a nitrogen atmosphere. The heating rate during the reaction was 5°C / min and the insulation time was 4h.

[0037] By subjecting the carbon cloth electrode modified with biomass materials to carbon thermal reaction, such as Figure 1As shown, the carbothermal reaction can form carbides embedded in the pores of the worm-like biomass on the electrode surface, increasing the redox area at the electrode and providing a richer effective area for chemical reactions.

[0038] The carbon cloth electrode modified with biomass materials was compared with the original unmodified material in battery cycle testing (coulombic efficiency, energy efficiency, voltage efficiency), and the comparison results are as follows: Figure 2 , Figure 3 and Figure 4 As shown, by comparison, the carbon cloth electrode modified with biomass material shows higher coulombic efficiency, energy efficiency, voltage efficiency, and more stable cycle performance in the battery cycle compared with the original unmodified material; it can effectively improve the electrochemical performance and catalytic activity of the electrode.

[0039] The electrochemical test results of the biomass material modified carbon cloth electrode material are shown in Figure 5 The oxidation peak and reduction peak of the electrode prepared in the figure also show more symmetry and less separation, showing strong electrocatalytic activity.

[0040] Example 2

[0041] The carbon cloth was cleaned with deionized water and then soaked in alcohol for 10 minutes. The carbon cloth was ultrasonically cleaned with deionized water for 10 minutes and placed in an oven to be dried at 95°C to remove impurities on the surface of the carbon cloth.

[0042] The carbon cloth was placed in a muffle furnace and subjected to a high temperature heat treatment at 500°C in air for 5 hours. 20 g of orange peel powder was added to 200.0 ml of deionized water and mixed with 10.0 ml of 0.15 M sucrose solution. The resulting mixture was stirred for 10 minutes and ultrasonically treated for 15 minutes to form a slurry, and the carbon cloth was immersed in the precursor slurry for 1 hour and then dried at 70°C.

[0043] The treated carbon cloth was placed in a tubular furnace high temperature device and subjected to high temperature heat treatment at 1200°C in a nitrogen atmosphere. The heating rate during the reaction was 5°C / min and the insulation time was 5h.

[0044] The electrochemical test results of the biomass material modified carbon cloth electrode material are shown in Figure 6 The oxidation peak and reduction peak of the electrode prepared in the figure also show more symmetry and less separation, showing strong electrocatalytic activity.

[0045] Example 3

[0046] The carbon cloth was cleaned with deionized water and then soaked in alcohol for 10 minutes. The carbon cloth was ultrasonically cleaned with deionized water for 10 minutes and placed in an oven to be dried at 85°C to remove impurities on the surface of the carbon cloth.

[0047] The carbon cloth was placed in a muffle furnace and subjected to a high temperature heat treatment at 540°C in air for 5 hours. 20 g of orange peel powder was added to 200.0 ml of deionized water and mixed with 10.0 ml of 0.1 M glucose solution. The resulting mixture was stirred for 10 minutes and ultrasonically treated for 15 minutes to form a slurry, and the carbon cloth was immersed in the precursor slurry for 1 hour and then dried at 75°C.

[0048] The treated carbon cloth was placed in a tubular furnace high temperature device and subjected to high temperature heat treatment at 1150°C in a nitrogen atmosphere. The heating rate during the reaction was 5°C / min and the insulation time was 5h.

[0049] The electrochemical test results of the biomass material modified carbon cloth electrode material are shown in Figure 7 .

[0050] Example 4

[0051] The carbon cloth was cleaned with deionized water and then soaked in alcohol for 10 minutes. The carbon cloth was ultrasonically cleaned with deionized water for 10 minutes and placed in an oven to be dried at 90°C to remove impurities on the surface of the carbon cloth.

[0052] The carbon cloth was placed in a muffle furnace and subjected to a high temperature heat treatment of 500°C in air for 4 hours. 20 g of lemon peel powder was added to 200.0 ml of deionized water and mixed with 10.0 ml of 0.1 M fructose solution. The resulting mixture was stirred for 15 minutes and ultrasonically treated for 15 minutes to form a slurry, and the carbon cloth was immersed in the precursor slurry for 2 hours and then dried at 85°C.

[0053] The treated carbon cloth was placed in a tubular furnace high temperature device and subjected to high temperature heat treatment at 1200°C in a nitrogen atmosphere. The heating rate during the reaction was 5°C / min and the insulation time was 5h.

[0054] The electrochemical test results of the biomass material modified carbon cloth electrode material are shown in Figure 8 Its hydrophilic properties are as follows Fig. 9 As shown in the figure, it can be seen that the hydrophilicity of the carbon cloth electrode modified by biomass material is significantly improved compared with the unmodified original electrode.

[0055] The method of the invention proposes a biomass material modification method for a carbon cloth electrode of an iron-chromium liquid flow battery, and the modified iron-chromium liquid flow battery electrode material is prepared by using the biomass material to improve the battery performance.

[0056] At the same time, biomass materials are widely available, inexpensive, and environmentally friendly, making them an ideal carbon cloth electrode modification material. By using biomass materials to modify and modify carbon cloth electrodes, the electrochemical performance and catalytic activity of the electrodes can be effectively improved. This has important research value and broad application prospects.

[0057] The biomass material modified carbon cloth electrode prepared by the present invention can enhance the electrochemical reaction activity of chromium ions by forming a nitrogen doping effect on the carbon cloth surface during biomass modification, while improving the energy efficiency of the iron-chromium liquid flow battery, slowing down the battery capacity decay, and improving the cycle stability performance. It is of great significance to the field of iron-chromium liquid flow battery electrode manufacturing and has excellent promotion and application prospects.

[0058] The operation method of the present invention is simple, the raw material cost is low, and the existing production process is fully capable of manufacturing the method of the present invention, which is easy to promote. It is a method for manufacturing electrode materials that can greatly promote the commercial development of iron-chromium liquid flow batteries and promote better commercial development of iron-chromium liquid flow batteries.

[0059] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. Unless otherwise specified, the means used in the specification are all existing technical means in the art.

[0060] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a biomass-modified iron-chromium liquid flow battery carbon cloth electrode, characterized in that: The steps include: S1. Carbon cloth pretreatment: The carbon cloth is cleaned with deionized water, soaked in ethanol after cleaning, and then ultrasonically cleaned in deionized water. The carbon cloth after ultrasonic cleaning is placed in an oven to dry, and then activated by high-temperature heat treatment; S2. Preparing a precursor slurry: adding biomass powder to deionized water, and then adding an auxiliary agent to obtain a mixture, stirring and ultrasonically treating the obtained mixture to form a precursor slurry; S3, impregnation: immersing the carbon cloth after high temperature heat treatment into the precursor slurry, using an impregnation method for treatment, and then drying the carbon cloth; S4, carbon thermal reduction: the carbon cloth obtained in step S3 is taken out, and carbon thermal reduction is performed by calcining at high temperature in a protective atmosphere in a tubular furnace to obtain a carbon cloth electrode modified by biomass material.

2. The method for preparing the biomass-modified iron-chromium liquid flow battery carbon cloth electrode according to claim 1, characterized in that: In step S1, the carbon cloth is polyacrylonitrile PNV-based carbon cloth, rayon-based carbon cloth or petroleum asphalt-based carbon cloth; the soaking time in ethanol is 10 to 20 minutes; the ultrasonic cleaning time is 10 to 100 minutes; and the drying temperature in the oven is 30 to 150°C.

3. The method for preparing the biomass-modified iron-chromium liquid flow battery carbon cloth electrode according to claim 1, characterized in that: In step S1, the high-temperature heat treatment of activated carbon cloth is to place the carbon cloth in a muffle furnace and perform high-temperature heat treatment in an atmosphere of one or more mixed gases of air, helium, nitrogen, argon, xenon, and neon; the temperature of the high-temperature heat treatment is 200-800°C, and the insulation time is 1-20h.

4. The method for preparing the biomass-modified iron-chromium liquid flow battery carbon cloth electrode according to claim 1, characterized in that: In step S2, the biomass powder is one or more of grapefruit peel powder, tangerine peel powder, orange peel powder, and lemon peel powder, and the mass fraction of the biomass powder in the final precursor slurry is 1% to 30%.

5. The method for preparing the biomass-modified iron-chromium liquid flow battery carbon cloth electrode according to claim 1, characterized in that: In step S2, the auxiliary agent is one or more of sucrose, glucose, lactose, and fructose, and the concentration is 0.1-5 mol / L.

6. The method for preparing the biomass-modified iron-chromium liquid flow battery carbon cloth electrode according to claim 1, characterized in that: In step S2, the stirring time is 10 to 100 minutes; the ultrasonic time is 10 to 100 minutes.

7. The method for preparing the biomass-modified iron-chromium liquid flow battery carbon cloth electrode according to claim 1, characterized in that: In step S3, the dipping time is 10 to 200 minutes; when the carbon cloth is dried, the drying temperature is 30 to 150° C., and the drying time is 1 to 20 hours.

8. The method for preparing the biomass-modified iron-chromium liquid flow battery carbon cloth electrode according to claim 1, characterized in that: In step S4, during carbon thermal reduction, the calcination temperature is 500-2000° C., the protective atmosphere is a mixed gas of one or more of helium, nitrogen, argon, xenon, and neon, the heating rate during the reaction is 1-30° C. / min, and the insulation time is 1-20 h.

9. An electrode material prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Macro biomass modified electrode material and preparation method thereof

    CN113571715A

  • Preparation method of biomass carbon cloth and membrane electrode

    CN115863665A

  • Method for modifying defects of carbon cloth electrode of iron-chromium flow battery

    CN116031418A

  • Preparation method and application of cellulose biomass all-vanadium redox flow battery electrode

    CN117039012A

  • Method for modifying modified battery carbon cloth electrode by metal carbide nano material

    CN117913301A

Cited By

  • Metal-organic framework derived gradient composite electrode with high selectivity as well as preparation method and application of metal-organic framework derived gradient composite electrode

    CN122091608A